Perspectives and Knowledge about Fertility Preservation Strategies among Female Cancer Patients in Turkey - Volkan Emirdar; Volkan Karataşli; Ferruh Acet; Gulin Okay; Funda Gode; Alaattin Karabulut; Çağatay Arslan (International Journal of Clinical Practice)
Objectives. To evaluate the knowledge level and perspectives of female cancer patients regarding fertility preservation techniques before gonadotoxic treatment. Material and Methods. This was a prospective observational survey-based study conducted between 2016 and 2020 in Izmir Economy University Medical Park Hospital. A total of 150 female cancer patients aged 18–42 years were included. The participants completed a 17-item questionnaire, developed by the research team to evaluate their knowledge and perspectives on fertility preservation techniques. Results. The mean age of the patients was 39.5 ± 4.9 years. Only 64.7% of the patients were referred to fertility counseling by a gynecologist, while 72.6% of the patients knew of the risk of infertility after cancer treatment. There was a significant correlation between the health status and cancer stage of the patient (p=0.003). The estimated future chance of becoming pregnant spontaneously or through fertility preservation techniques was significantly higher in patients with a higher education level (p=0.041 or 0.008, respectively). Satisfaction with the counseling process was reported as high or low by 66.7% or 20% of the patients, respectively. Conclusions. The rate of referral of reproductive-age cancer patients to fertility preservation counseling is still not satisfactory. Education level was the only variable significantly associated with a motivation to become pregnant after cancer treatment, either spontaneously or through fertility preservation techniques.